PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA PERSETUBUHAN ANAK DALAM STUDI PUTUSAN NOMOR 161/Pid.Sus/2021/PN Wkb - Sherly Yahrotul Mutimah; Dara Pustika Sukma (Verstek, 2026)
Abstract: This study aims to find out  the judge's consideration in imposing a sentence.in the trial of a child copulation case in Verdict Number 161/Pid.Sus/2021/PN Wkb This research was a normative legal research with prescriptive and applied nature. This research used a case study. The technique of collecting primary and secondary legal materials was carried out by literature study, then analyzed by syllogism deduction and conclusions were drawn from major premises which were then connected to minor premises. The judge's consideration in deciding the case of the crime of child copulation in Verdict Number 161/Pid.Sus/2021/PN Wkb is in accordance with Article 183 of the Criminal Procedure Code. This is because in the trial there were 3 (three) pieces of evidence (RSUD Number.511/334/VER/63.L/08/2021).